PENGUATAN IDENTITAS DIGITAL ORGANISASI KEMAHASISWAAN MELALUI PELATIHAN DESAIN BRANDING BERBASIS INKSCAPE - Yunus Anis; Hersatoto Listiyono; Sunardi; Sri Mulyani; Vici Tiara Anjarsari (CV. Nature Creative Innovation, 2025)
This community service activity aims to strengthen the digital identity of student organizations through Inkscape-based branding design training as an effective and accessible open-source solution. Many student organizations face challenges such as inconsistent visual quality, unrepresentative logos, and publication designs that do not reflect the organization's character. Through an interactive workshop approach, participants were trained to understand modern branding concepts, visual identity principles, and techniques for creating design elements including logos, color palettes, typography, and digital publication templates. The results of the activity showed a significant increase in participants' abilities in designing more professional and consistent brand kits. The resulting designs have also been successfully used in the organization's official publications, thus directly impacting the image and appeal of their digital communications.